Interaction of Lysozyme with 6-Amino-4-aryl-5-cyano- 3-methyl-1-phenyl-1,4-dihydropyrano[2,3-c]pyrazole: A Fluorescence Auenching Study - WU, HUI; CHEN, XIU-MEI; WAN, YU; LIAN, SHU-QIN; YE, LING (Asian Journal of Chemistry, 2010)
The interactions between 6-amino-4-aryl-5-cyano-3-methyl-1-phenyl- 1,4-dihydropyrano[2,3-c]pyrazole and lysozyme (LYSO) were studied by using tryptophan fluorescence quenching and 6-amino-4-(2- hydroxyphenyl)-5-cyano-3-methyl-1-phenyl-1,4-dihydropyrano[2,3-c] pyrazole (1) was studied in detail because of its best quenching efficiency and biggest water solubility. At different temperatures, quenching constants KSV, binding constants K and binding sites n of LYSO with 1 were determined and thermodynamic parameters were calculated. The distance r between tryptophane residues and 1 was obtained according to the Forster mechanism of non-radiation energy transfer. Furthermore, synchronous fluorescence spectroscopy data suggested that the association between 1 and LYSO changed the molecular conformation of LYSO and the hydrophobic interaction played a major role. It was proved that the fluorescence quenching of LYSO by 1 was related to the formation of a 1-LYSO complex and the nonradiation energy transfer.